Reimagining Service-Learning: Deepening the Impact of This High-Impact Practice. (September 2019) - Anderson, Karen L.; Boyd, Margaret; Ariemma Marin, Katherine; McNamara, Kathleen
Background: Service-learning has historically been seen as a high-impact practice that empowers undergraduates to develop essential learning outcomes. Most service-learning discussed within the literature occurs as a required element of a credit-bearing academic course.Purpose: This study explored what happens when service-learning is reimagined to be disconnected from a specific course and credit hours, and available via application to all undergraduates regardless of the liberal arts/science major or year in the college.Methodology/Approach: HyperRESEARCH was used to identify themes and categories from 45 sets of weekly reflections submitted by 36 participants engaged in reimagined service-learning projects across five semesters.Findings/Conclusions: Key findings reveal that not only do undergraduates develop essential learning outcomes as delineated in the existing literature, but in many cases, their understandings, and abilities to execute these skills, are deepened when service-learning is reimagined. Findings also reveal that undergraduates may experience service-learning differently depending upon year in college.Implications: Results from this study suggest that practitioners should investigate ways to reimagine service-learning, with specific emphasis placed on the differential ways college students at various stages in their undergraduate career experience, and learn from, service-learning.